An Algorithm for Inter-Modulation Interference Suppression Based on Frequency Optimization - Zhidong Hu; Weichao Zeng; Zhuoyi Tang (Dianxin kexue)
The mechanism of the fifth-order inter-modulation was discussed,and a frequency optimization algorithm for reducing the network inter-modulation interference was proposed.The inter-modulation interference produced by frequency combination can be suppressed when the TCH frequencies combination of the cell meets the following requirement:935×106≤fmin＜fmax≤954×106Hz,and the difference between the maximum number and minimum number of frequency points is less than 65.This method can suppress the inter-modulation interference from the source,and provides an innovative idea for inter-modulation interference optimization.